Double Certificates as Land Administration Defects: Parameters for Cancellation According to Government Regulation 18/2021 and Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21/2020 and Their Legal Consequences - Sarah Atikasari; Suhadi Suhadi (Jurnal Daulat Hukum, 2026)
This article discusses double/overlapping certificates as land administration defects and examines the parameters for their cancellation according to Government Regulation 18/2021 and Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21/2020, while also testing how these parameters actually work in practice and court decisions. The objectives of this study are (1) to systematize the normative parameters for the cancellation of duplicate certificates as a "gateway, requirements, and safeguards" for administrative authority, (2) to formulate applicable parameters in the form of indicators of proof used in ATR/BPN practice and litigation forums (PTUN/civil) to determine which certificates should be canceled, and (3) to analyze the legal consequences of cancellation on the status of rights, the control of registration data, and the protection of third parties. This study uses a normative (doctrinal) legal method with a legislative, case, and conceptual approach; primary legal materials include Government Regulation 18/2021, Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21/2020, as well as chamber/SEMA formulations and relevant decisions; secondary materials are in the form of books and journal articles. The analysis was conducted qualitatively and normatively through the classification of legal materials, interpretation and construction of norms to develop normative parameters, reading of decisions/formulations to develop a checklist of applicable indicators (physical control, good faith, history of rights, procedural compliance, and forum selection), and drawing deductive conclusions. The results of the study show that normative parameters provide a framework for administrative correction, but in their application they shift to become operational parameters that determine the evidence and direction of the settlement forum, especially when there is a transfer of rights, a third party acting in good faith, or a burden of encumbrance. The novelty of this research lies in the systematic mapping and linking of two layers of parameters (normative-applicative) as operational measures for the cancellation of double certificates and their legal consequences in order to be more consistent and predictive.